1997
DOI: 10.1023/a:1018834723417
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The immunosuppressive agent cyclosporin A (CsA) is known to cause cholestasis. Transcellular and paracellular transport of macromolecules contribute, albeit to a minor extent, to bile formation, but little is known about the effects of CsA on these pathways. The aims of this study were to investigate the influence of CsA on tight junction (paracellular) permeability and on transcytotic vesicular pathways labeled with horseradish peroxidase (HRP) in perfused rat liver. Livers from male Sprague-Dawley rats were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Although HRP appeared in bile roughly at the same time as FITC-dextran, the secretion rate revealed two peaks at 7 minutes and 15 minutes, respectively. These two peaks were seen irrespective of the HRP concentration perfused through the liver (0.08; 0.8; 8 mg/mL) and are in agreement with data from different laboratories [7, 8, 20, 21]. The bile flow, shown in Figure 2(b), remained constant at 1.6  μ L/g liver and min throughout this perfusion.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Although HRP appeared in bile roughly at the same time as FITC-dextran, the secretion rate revealed two peaks at 7 minutes and 15 minutes, respectively. These two peaks were seen irrespective of the HRP concentration perfused through the liver (0.08; 0.8; 8 mg/mL) and are in agreement with data from different laboratories [7, 8, 20, 21]. The bile flow, shown in Figure 2(b), remained constant at 1.6  μ L/g liver and min throughout this perfusion.…”
Section: Resultssupporting
confidence: 89%
“…In contrast, we could demonstrate mannan inhibitable HRP secretion at 0.8 mg/mL. Thus, when HRP is applied at concentrations ranging between 1 mg/mL and 10 mg/mL as in morphological and perfusion studies [7, 8, 20, 21, 46] the proportion due to receptor-mediated endocytosis cannot be ignored, although at such HRP concentrations uptake by isolated hepatocytes is mainly by a fluid-phase mechanism.…”
Section: Discussionmentioning
confidence: 71%
“…Thus, we suggest that pharmacologic doses of cyclosporine may induce an increase of occludin expression and a decrease in TER. Similarly, Lora et al [34] have demonstrated that, in the rat liver, low doses of cyclosporine significantly increase the paracellular permeability across the TJ. Cyclosporine-induced increases in TJ permeability have also been demonstrated in rat hepatocyte couplets [35].…”
Section: Discussionmentioning
confidence: 85%
“…It occurs in bile-duct ligation [142,152] and under conditions of oxidative stress induced by both menadione [148,153] and tert-butylhydroperoxide [154,155]. It is also impaired in several models of druginduced cholestasis, such as those induced by administration of E 2 17G [148,156], cyclosporin A [148,157], acetaminophen [158], cholephilic dyes [159], carmustine [160], alpha-naphthylisothiocyanate [161] and LC [127], or its cholestatic conjugate, TLC [148,162]. In human hepatopathies, substantial alterations of tight-junctional proteins occur in primary biliary cirrhosis (predominantly in bile ducts) and in primary sclerosing cholangitis (predominantly in hepatocytes) [163].…”
Section: Impairment Of Tight Junctional Permeabilitymentioning
confidence: 99%